2005
DOI: 10.1128/aac.49.10.4382-4385.2005
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-Resistant Enterococcus faecium Strains Isolated from Community Wastewater from a Semiclosed Agri-Food System in Texas

Abstract: Vancomycin-resistant Enterococcus faecium strains (VRE) were isolated from human wastewater but not swine fecal waste from a semiclosed agri-food system in Texas. Forty-nine VRE isolates possessed vanA, and one possessed vanB. Twenty-one pulsed-field gel electrophoresis types were identified and segregated into three groups. There was evidence of clonal dissemination among geographically separated sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…One of these patients came in for her annual check-up and had no prior healthcare exposures 28 . Also, VRE was found in wastewater from a semi-closed agri-food system 29 . Nonetheless, VRE remains an uncommon pathogen in community-associated infections.…”
Section: Vancomycin-resistant Enterococci (Vre)mentioning
confidence: 99%
“…One of these patients came in for her annual check-up and had no prior healthcare exposures 28 . Also, VRE was found in wastewater from a semi-closed agri-food system 29 . Nonetheless, VRE remains an uncommon pathogen in community-associated infections.…”
Section: Vancomycin-resistant Enterococci (Vre)mentioning
confidence: 99%
“…Many surveillance studies failed to recognize a considerable reservoir of vanB among enterococcal colonizers in animals and humans, whereas recent real-time based studies targeting vanB or improved methods of detection revealed a considerable reservoir among intestinal colonizers, maybe also non-enterococcal bacteria (see above). In general, the supposed low expression of vancomycin resistance among vanB strains may have lead to an underestimation of its general prevalence, since in many screening studies comparably high vancomycin concentrations were used to select VRE (Poole et al, 2005;Hershberger et al, 2005). Rates of clinical vanB-type VRE are increasing, at least in some European countries www.intechopen.com during last years Soderblom et al, 2010;Bourdon et al, 2011) and a link to a supposed reservoir outside the clinical setting, for instance, among mammal intestinal colonizers is discussed also in areas where vanB-type vancomycin resistance is more prevalent (Christiansen et al, 2004;Johnson et al, 2010).…”
Section: Localization and Spread Of Vana-and Vanb-type Resistancementioning
confidence: 99%
“…Waste received from environments under significant antibiotic pressure, such as hospitals, consistently contains a greater proportion of singly and multiple drug-resistant bacteria [9,22,26,28,38,60] and AR enterococci are commonly recovered from sewage [2,8,9,28,38,47,51,55]. House flies and other filth flies often have direct and unhindered access to many steps in the waste processing flow and therefore may acquire bacteria associated with the waste.…”
Section: Introductionmentioning
confidence: 99%